Trastorno somatomorfo y síntomas somático múltiples en los adultos mayores del Centro Gerontológico de Quevedo - Solorzano Figueroa, Cristhian Javier (2019)
This work focuses on the reality that occurs during the third stage of life "old age" where older adults are faced with various health problems, which affect their daily lives, one of these problems with what is face these people is the presence of somatoform disorder, which is presented through different somatic symptoms that affects the adult, what is known about this disorder is that, despite the years that have passed since its appearance is not known to science certain that causes the presence of these symptoms that are confused with different pathologies presented in adulthood The objective of this research is to generate knowledge to the gerontological community about the somatoform disorder, since its symptoms are often confused with another type of pathology, stimulating older adults to participate daily in the activities that take place in the establishment. Encourage the habit of exercise in the elderly to improve their physical and mental health and is even essential as it can become a task to enjoy as a family and get closer or have a fun time with friends, can encourage physical activity in the daily life of older adults by carrying out adapted activities that youth liked to perform.